2017
DOI: 10.1186/s12943-017-0654-3
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic down regulation of G protein-coupled estrogen receptor (GPER) functions as a tumor suppressor in colorectal cancer

Abstract: BackgroundEstrogenic signals are suggested to have protection roles in the development of colorectal cancer (CRC). The G protein-coupled estrogen receptor (GPER) has been reported to mediate non-genomic effects of estrogen in hormone related cancers except CRC. Its expression and functions in CRC were investigated.MethodsThe expression of GPER and its associations with clinicopathological features were examined. The mechanisms were further investigated using cells, mouse xenograft models, and clinical human sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
85
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 43 publications
7
85
1
4
Order By: Relevance
“…Some kind of estrogens might modulate immune response, probably through G protein-coupled estrogen receptor pathway. [34] A similar observation was reported in melanoma. [35] Female patients usually had better prognosis over male, while high BMI There was view that for male obese patient good prognosis is because of the increase of hormone led by obesity according to earlier reports.…”
Section: Discussionsupporting
confidence: 71%
“…Some kind of estrogens might modulate immune response, probably through G protein-coupled estrogen receptor pathway. [34] A similar observation was reported in melanoma. [35] Female patients usually had better prognosis over male, while high BMI There was view that for male obese patient good prognosis is because of the increase of hormone led by obesity according to earlier reports.…”
Section: Discussionsupporting
confidence: 71%
“…Some studies show that ERβ is inversely correlated to prognosis although not all agree with this finding [37,38]. Liu et al [39] found that higher GPR30 expression in CRC tissue is associated with a better survival compared to lower GPR30 expression. However, further study is required to identify whether GPR30 is upregulated or downregulated in different patient cohorts and whether this can be used as a prognostic or therapeutic marker.…”
Section: Reproductive Systemmentioning
confidence: 99%
“…Liu and colleagues study shows that GPER mRNA and protein expression is downregulated in CRC compared to matched normal tissue and this downregulation is associated with poorer prognosis 100 . Published data from our lab support the fact that GPER mRNA levels are decreased in human CRC tissue compared to matched normal tissue.…”
Section: Discussionmentioning
confidence: 99%